How do you simplify # 5xy - 6x^2y^2 + 4x^2y^2 - 2xy#?

2 Answers
Jun 13, 2017

Answer:

See a solution process below:

Explanation:

First, group and combine like terms:

#5xy - 6x^2y^2 + 4x^2y^2 - 2xy =>#

#-6x^2y^2 + 4x^2y^2 + 5xy - 2xy =>#

#(-6 + 4)x^2y^2 + (5 - 2)xy =>#

#-2x^2y^2 + 3xy#

Now, factor an #xy# out of each term:

#(xy * -2xy) + (3 * xy) =>#

#xy(-2xy + 3)#

Jun 13, 2017

Answer:

#-xy(2xy-3)#

Explanation:

You would collect equal variables together

#(5xy - 2xy)+(-6x^2y^2 + 4x^2y^2)#

Simplify it

#5xy - 2xy = 3xy#
#-6x^2y^2 + 4x^2y^2 = -2x^2y^2#

#3xy -2x^2y^2#

Factorise it by taking a common factor which is #-xy#

#-xy(2xy-3)#